Formulation and test of physical properties of eyeshadow cream with natural dyes of Kasumba turate flower extract (Carthamus tinctorius L.) - Lallita; Mohammad Zaky; Hilda Damayanti (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2024)
Safflower (Carthamus tinctorius L.) contains two natural pigments,, namely yellow carthamin and orange-red carthamin dye which are used as natural dyes. The research aimed to see whether safflower extract could be used as a natural coloring in eyeshadow cream and the physical properties of eyeshadow cream. The 70% ethanol extract of safflower was formulated into lip cream preparations, with varying concentrations of 0% (K-), 1% (F1), 2% (F2), and 3% (F3). Testing the physical properties of the preparation, namely the organoleptic test, homogeneity test, pH test, type of cream test, spread test, spreadability test, viscosity test, and hedonic test. The formulation of the lip cream of safflower extract showed a distinctive smell of orange essence, yellow to brownish yellow color, semi-solid form, homogeneous preparation until the 28th day, easy to apply, had a pH (4.5-7.0), type cream O/W, has a viscosity of 10,000-20,000 cPs and spreadability of 5-7 cm. This study concludes that Safflower extract can be used as a natural dye in Eyeshadow cream preparations and meets the requirements of good physical properties of Eyeshadow cream preparations.